Controlled Shape Evolution of Pure‐MOF 1D Microcrystals towards Efficient Waveguide and Laser Applications. Issue 10 (12th January 2021) - Lv, Yuanchao; Xiong, Zhile; Yao, Yinan; Ren, Ang; Xiang, Shengchang; Zhao, Yong Sheng; Zhang, Zhangjing
Abstract: MOF‐based one‐dimensional materials have received increasing attention in the nanophotonics field, but it is still difficult in the flexible shape evolution of MOF micro/nanocrystals for desired optical functionalities due to the susceptible solvothermal growth process. Herein, we report on the well‐controlled shape evolution of pure‐MOF microcrystals with optical waveguide and lasing performances based on a bottom‐up and top‐down synergistic method. The MOF microcrystals from solvothermal synthesis (bottom‐up) enable the evolution from microrods via microtubes to nanowires through a chelating agent‐assisted etching process (top‐down). The three types of MOF 1D‐microstructures with high crystallinity and smooth surfaces all exhibit efficient optical waveguide performance. Furthermore, MOF nanowire with lowest propagation loss served as low‐threshold pure‐MOF nanolasers with Fabry–Pérot resonance. These results advance the fundamental understanding on the controlled MOF evolution mechanism, and offer a valuable route for the development of pure‐MOF‐based photonic components with desired functionalities. Abstract : The shape evolution of pure‐MOF 1D‐microcrystals with ideal nanophotonics functions was firstly achieved based on a bottom‐up/top‐down synergistic method. These microcrystals enable evolution from microrods via microtubes to nanowires with efficient optical waveguide and laser applications.